PENGARUH INOVASI PRODUK DAN ORIENTASI PASAR TERHADAP KEUNGGULAN BERSAING CELANA MEREK JEANS DI JAKARTA - Iwan Kurniawan Subagja (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to analyze the effect of product innovation and market orientation on competitive advantage on Jeans brands in Kebayoran Lama, South Jakarta. This study used survey research type with a sampling method saturated with the number of respondents as many as 30 respondents. Data analysis used multiple linear regression. The results showed that there was a significant influence between product innovation and market orientation on the competitive advantage of jeans brand in Kebayoran Lama Jakarta. Product innovation is something that can be seen as a functional advancement of a product that can take the product one step further than competitors' products. Likewise, market orientation can find out the needs and desires of consumers, so that it can make a competitive advantage over the products being marketed.